Preferensi Konsumen Memilih Produk Mie Instan (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Pratama, Dimas Raka Setya; Khalikussabir, Khalikussabir; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to: 1. Explain which combination of attributes influences consumer preferences when choosing instant noodle products. 2. Describe which product attributes are important to consumers when choosing instant noodle products. 3. Explain which levels of instant noodle product attributes are most important to consumers when choosing instant noodle products. The sampling technique used was a non-probability sampling technique, and data from 96 respondents were obtained. The data analysis technique used in this research was Conjoint Analysis. The results of the research show that: 1. The combination of attributes considered most important is having a delicious and savory aroma, affordable price, and attractive packaging design. 2. The attributes based on importance are taste attribute, price attribute, and packaging attribute. 3. The most important attribute levels are affordable price, delicious and savory aroma, and attractive packaging design. Keywords: Preference, Price, Taste, Packaging